Fate of H2S during the cultivation of Chlorella sp. deployed for biogas upgrading. (15th April 2017) - González-Sánchez, Armando; Posten, Clemens
Abstract: The H2 S may play a key role in the sulfur cycle among the biogas production by the anaerobic digestion of wastes and the biogas upgrading by a microalgae based technology. The biogas is upgraded by contacting with slightly alkaline aqueous microalgae culture, then CO2 and H2 S are absorbed. The dissolved H2 S could limit or inhibit the microalgae growth. This paper evaluated the role of dissolved H2 S and other sulfured byproducts under prevailing biogas upgrading conditions using a microalgal technology. At initial stages of batch cultivation the growth of Chlorella sp. was presumably inhibited by dissolved H2 S. After 2 days, the sulfides were oxidized mainly by oxic chemical reactions to sulfate, which was later rapidly assimilated by Chlorella sp., allowing high growing rates. The fate of H2 S during the microalgae cultivation at pH > 8.5 was assessed by a mathematical model where the pentasulfide, thiosulfate and sulfite were firstly produced and converted finally to sulfate for posterior assimilation. Highlights: At H2 S > 200 ppmv inhibited the microalgae growth of Chlorella sp. Bicarbonate reduced the specific growth rate of Chlorella sp. Sulfide was chemically converted to sulfate after two days of batch cultivation. Chlorella sp. assimilated in situ the sulfate chemically produced. A novel H2 S oxidation with sulfate assimilation pathway was proposed.